Relationships between transporter expression and the status of BRAF V600E mutation and F-18 FDG uptake in papillary thyroid carcinomas. (2nd January 2016) - Yoon, Minki; Jung, Soo Jin; Kim, Tae Hyun; Ha, Tae Kwun; Urm, Sang-Hwa; Park, Ji Sun; Lee, Seok Mo; Bae, Sang Kyun
Abstract: Purpose : The purpose of this study was to evaluate the expression of the glucose transporters GLUT1 and GLUT3 in papillary thyroid carcinomas (PTCs) and to elucidate their relationship with the BRAF V600E mutation and F-18 FDG uptake. Materials and methods . We retrospectively analyzed data of 52 PTC patients (41 women and 11 men; mean age, 52.4 ± 14.5 years). F-18 FDG PET/CT was performed preoperatively, and the maximum standardized uptake value (SUVmax) was calculated. GLUT1/GLUT3 expression was determined immunohistochemically, and the BRAF V600E mutation was detected using DNA sequencing. Results : GLUT1 and GLUT3 were expressed in 82.7% (43/52) and 59.6% (31/52) PTCs, respectively. The BRAF V600E mutation was detected in 65.4% (34/52) PTCs. The odds ratio between GLUT1 expression and the BRAF V600E mutation was 5.2 (95% CI, 1.11–24.05; p < 0.05), and that between GLUT3 expression and the BRAF V600E mutation was 3.8 (95% CI, 1.14–12.53; p < 0.05). The SUVmax of PTCs was significantly higher if they carried the BRAF V600E mutation (11.3 ± 2.0, compared with 5.7 ± 1.4 for wild type BRAF tumors, Mann–Whitney test, p = 0.016). Neither GLUT1 nor GLUT3 expression was significantly associated with the SUVmax of F-18 FDG PET/CT in PTCs. Conclusions : Our findings confirmed that both GLUT1 and GLUT3 are strongly expressed by PTCs, although their expression was not significantly associated with the SUVmax of F-18 FDG PET/CT. However, GLUT1 and GLUT3 expressions were significantly associated with the presence of the BRAF V600E mutation, and the SUVmax of tumors was significantly higher in the presence of the mutated BRAF gene.